2018
DOI: 10.1109/ted.2018.2791959
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Electrothermal Simulation of a 3-D Fin-Shaped Field-Effect Transistor Based on GaN Nanowires

Abstract: In recent years, three-dimensional GaN-based transistors have been intensively studied for their dramatically improved output power, better gate controllability, and shorter channels for speedup and miniaturization. However, thermal analysis of such devices is often oversimplified using the conventional Fourier's law and bulk material properties in thermal simulations. In this aspect, accurate temperature predictions can be achieved by coupled phonon and electron Monte Carlo simulations that track the movement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In calibrations for bulk Si, the electron MC simulations yield electrical conductivities within 5% divergence from the theoretical predictions at 300-500 K. The same code has also been well calibrated for the high-electric-field electron mobility of bulk GaN or two-dimensional electron gas within GaN-based transistors, where good agreement can be found between the simulations and experimental results. [32][33][34] In this work, the electrical conductivity of periodic two-dimensional nanoporous Si films with pore-edge-trapped charges is simulated. The computational domain is a 60 nm × 60 nm square as a single period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In calibrations for bulk Si, the electron MC simulations yield electrical conductivities within 5% divergence from the theoretical predictions at 300-500 K. The same code has also been well calibrated for the high-electric-field electron mobility of bulk GaN or two-dimensional electron gas within GaN-based transistors, where good agreement can be found between the simulations and experimental results. [32][33][34] In this work, the electrical conductivity of periodic two-dimensional nanoporous Si films with pore-edge-trapped charges is simulated. The computational domain is a 60 nm × 60 nm square as a single period.…”
Section: Resultsmentioning
confidence: 99%
“…31 For TE interests, electron MC simulations have been performed on width-modulated nanowires, 22 a one-dimensional chain of grains with a potential barrier at each grain boundary, 23 polycrystalline ceramics, 26 a Si nanostructure with periodic barrier layers. 27 For general applications, such electron MC simulations have also been applied to high-power GaN-based devices [32][33][34] and heterostructures. 24,25,28 In electron MC simulations, one period of the nanostructure is created as the computational domain (Fig.…”
Section: Overview Of the Electron MC Simulationmentioning
confidence: 99%
“…The thicknesses of the top MC zone, bottom MC zone and overlap zone are denoted as t topMC , t botMC and t o . Compared with the hybrid BTE-Fourier methods in [43][44][45][46], there is an additional bottom MC zone, of which the necessity will be explained in Sec. 3.1 Phono MC simulation and the finite element method (FEM) based on Fourier's law are coupled by an alternating technique in the hybrid method.…”
Section: Methodsmentioning
confidence: 99%
“…By solving phonon Boltzmann transport equation (BTE) in a small domain of the device channel and utilizing Fourier's law in the rest domain, Donmezer and Graham [10] found that the hotspot temperature is higher when the ballistic-diffusive transport effect is considered. Hao et al [43] combined phonon MC and Fourier's law in a similar way to simulate two-dimensional (2D) GaN HEMTs, then the method was applied to more complex structures [44,45]. Chatterjee et al [46] proposed a phonon BTE -Fourier coupled thermal modeling to study the interplay of heat concentration and ballistic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although great efforts have been devoted to multiscale simulation techniques to predict the temperature profile of devices [26]- [28], little work has analyzed the thermal spreading process and the influences of ballistic effects in detail [24]. In addition, these simulations often take a long time to converge, and when considering phonon dispersion, they can be much more time-consuming [29].…”
Section: Introductionmentioning
confidence: 99%